2016
DOI: 10.1016/j.engstruct.2016.01.017
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the Equivalent Geometric Nodal Imperfections on the stability of single layer grid shells

Abstract: The present paper discusses the sensitivity of the global and local stability of a hybrid single layer grid shell to a set of equivalent geometric nodal imperfections representative of the actual structural and construction imperfections. Since imperfections are hard to be measured and controlled in experimental facilities, the stability of the structure is extensively investigated in numerical experiments. The imperfections are set by means of the so-called Eigenmode Imperfection Method. The method parameter … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(9 citation statements)
references
References 15 publications
0
9
0
Order By: Relevance
“…A more complete study using finite element analysis to evaluate local node stiffness of patented connections has been performed by Huang et al [19]. Bruno et al assessed the influence of nodal imperfection and of Eigenmode Imperfection Method (EIM) more recently [20]. Malek et al [15] performed numerical investigations on the buckling of spherical cap domes and considered geometrical values, like grid spacing, or height over span ratio, as parameters.…”
Section: Numerical Experimentsmentioning
confidence: 99%
See 1 more Smart Citation
“…A more complete study using finite element analysis to evaluate local node stiffness of patented connections has been performed by Huang et al [19]. Bruno et al assessed the influence of nodal imperfection and of Eigenmode Imperfection Method (EIM) more recently [20]. Malek et al [15] performed numerical investigations on the buckling of spherical cap domes and considered geometrical values, like grid spacing, or height over span ratio, as parameters.…”
Section: Numerical Experimentsmentioning
confidence: 99%
“…However, different studies show that other imperfections shapes should be considered, as they result in a bigger reduction of the buckling capacity of gridshells. Examples of such shapes can be found in [6] with the use of dynamic eigenmodes, and a discussion on the choice of appropriate imperfections is proposed in [20]. It has to be noticed that there is no closed-form solution on the worst imperfection possible, some studies even demonstrated that higher order eigenmodes can have a more critical effect on the reduction of buckling capacity [27].…”
Section: Imperfectionsmentioning
confidence: 99%
“…Shell structures are widely used in large-span public construction owing to its novel shape, low dead weight, and excellent mechanical behavior. However, initial geometric imperfections, an inevitable phenomenon due to machining and construction errors, considerably influence the buckling of shell structures [1][2][3][4].…”
Section: Introductionmentioning
confidence: 99%
“…The magnitude of maximum nodal imperfection was set to 50 mm and 100 mm. Bruno et al [21] investigated the sensitivity of the global and local stability of a hybrid single-layer grid shell to a set of equivalent geometric nodal imperfections, which represents the actual structure and construction imperfections.…”
Section: Introductionmentioning
confidence: 99%